INTERPRETIVE STRUCTURAL MODEL OF YOUTH-BASED WASTE MANAGEMENT ENABLERS IN LABUHAN BAJO VILLAGE, INDONESIA - Eni Hidayati; Ida Ansharyani; Lalu Kukuh Mahendra; Mahardika Rizqi Himawan (Forestry Study Program University Of Mataram, 2022)
Many policies, programs, and projects have been attempted to resolve waste problem in Indonesia, yet it is still one of the major environmental problems in the country. Several waste management practices exist at various levels, from the community level up to the industrial level. With increasing budget available for villages through various schemes, village-level management poses opportunities to solve waste problem in Indonesia. This empirical study uses Interpretive Structural Model (ISM) to examine variables contributed to youth-based waste management practice in Labuhan Bajo Village and the relationships among the variables. Participant observations and in-depth interviews were carried out to solicit information on important enablers for youth-based waste management. The model was developed using ten enablers. In this study, the model shows that the first driving power (at the bottom of the ISM) is facilitation, in this case, a NGO. On top of the model is the financial gain enabler. The MICMAC analysis shows that most of the enablers are in quadrant III (Linkages) category. Effective and efficient handling of the linkage enablers is necessary for youth-based waste management. This study offering enablers’ model gained from empirical study may offer fruitful insight for enhanced scholarship in waste management model at village level led by the local youth particularly in Indonesian context.